The influence of corporate governance and firm's characteristics on the extent of compliance with MASB standards among Malaysian listed companies - Abdul Rahman, Azhar (Maryland Institute of Research (MIR), 2011)
This paper contributes to our understanding of compliance with mandatory accounting standards. Specifically, we examine the efficacy of agency related mechanisms on the degree of disclosure compliance with the Malaysian Accounting Standards Board (MASB) accounting standards. Using data drawn from a sample of 170 Malaysian companies listed on the Kuala Lumpur Stock Exchange (KLSE) in 2004, we show that although overall disclosure compliance is high (85.2% of the items of information being disclosed), companies do not fully comply with MASB 10 (Accounting for leases), MASB 11 (Consolidated financial statements and investments in subsidiaries), MASB 12 (Investments in Associates), MASB 15 (Property, plant and equipment), MASB 20 (Provisions, contingent liabilities and contingent assets), MASB 24 (financial instruments), MASB 27 (Borrowing costs) and MASB 29 (Employee benefits).We employ an ordinary least square (OLS) regression model to establish whether selected company specific and corporate governance characteristics (proxying for agency-related mechanisms) are related to the degree of disclosure compliance. Our results indicate that only leverage is positively associated with the degree of compliance.The other variables consisting of board independence, audit committee independence, the existence of qualified accountant in the audit committee, CEO duality, the extent of outside block holders’ ownership, firm size and profitability do not show any significant relationship with degree of compliance.These results have important implications for policy because they suggest that whilst agency-related mechanisms may motivate compliance with mandatory standards, full compliance may be unattainable without regulations.